(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article examines the formation models and functional characteristics of units with the “eco-” prefix in the Uzbek language. It analyzes the role of prefixation in the development of ecological terminology, the semantic load of the “eco-” component, and its usage across different domains. The study also explores the lexical-semantic features of eco-units and their activity in modern ecological discourse.